Ethnocultural empathy and electronic word-of-mouth trust: shaping consumer boycott intention - Soong, Ru Yee (2024)
The purpose of this research is to investigate the extent to which attitudes, subjective norms, and perceived behavioural control (independent variables) influence the intention to boycott (dependent variable) in light of the conflict between Israel and Palestine, while also being moderated by ethnocultural empathy and electronic word of mouth trust (moderating variables).